Petrography and geochemical framework of guÃ©bakÃ© dolerites dyke swarms (north Cameroon, central Africa) - Togo, Abondou; Oumarou Faarouk, Nkouandou; Tefogoum Ghislain, Zangmo; Mefire Aminatou, Fagny; Dawai, Daouda; Appoliaire, Dinamou; Dagwai Justin, Guihdama; Haman, Adama (International Journal of Advanced Geosciences, 2022)
Dolerites dykes of 4.5 to 25 m wide extend from 200m to 1km, crosscut the GuÃ©bakÃ© granitoids basement in northern Cameroon along EW to N100E directions. Petrographic studies reveal the microlitic porphyritic texture to classical doleritic texture of ophitic to sub-ophitic types. GuÃ©bakÃ© dolerites are mainly composed in various proportions of skeletal plagioclase and feldspar, clinopyxene, amphibole and oxides crystals. ICP-MS and ICP-AES geochemical analyses have distiguished a lava series composed of trachybasalts, basaltic trachyandesites, trachyandesites, trachytes and rhyolites of continentale tholeiites affinity. Lavas have been differenciated trough fractional crystallization process coupled with crustal contamination and metasomatism. GuÃ©bakÃ© dolerites are products of relatively high partial melting rate of E-MORB mantle component. They stand as fingerprints of the post pan African crustal consolidation and precursor of the development of central African rift system at Cretaceous times.Â Â